The processes, logics and economies of violence in organised crime - Kotzé, Justin (Trends in organized crime, 2022)
This paper provides an introduction to the articles that comprise this special issue on violence and organised crime. Bringing together research into money laundering, local elections, state interventions and interrelated processes, firearms and home robberies, enforcers and contract killings, this issue explores the relationship between violence and various facets of organised crime. Taken together, the articles offer empirical and theoretical insights into the processes, logics and economies of violence. In doing so, this issue both advances our current understanding of the role violence plays in organised crime and raises additional questions about the context within which violence is employed, thereby highlighting further avenues for future research.